Regulation of the germinal center gene program by interferon (IFN) regulatory factor 8/IFN consensus sequence-binding protein - Lee, Chang Hoon (The Rockefeller University Press, 2006)
Interferon (IFN) consensus sequence-binding protein/IFN regulatory factor 8 (IRF8) is a transcription factor that regulates the differentiation and function of macrophages, granulocytes, and dendritic cells through activation or repression of target genes. Although IRF8 is also expressed in lymphocytes, its roles in B cell and T cell maturation or function are ill defined, and few transcriptional targets are known. Gene expression profiling of human tonsillar B cells and mouse B cell lymphomas showed that IRF8 transcripts were expressed at highest levels in centroblasts, either from secondary lymphoid tissue or transformed cells. In addition, staining for IRF8 was most intense in tonsillar germinal center (GC) dark-zone centroblasts. To discover B cell genes regulated by IRF8, we transfected purified primary tonsillar B cells with enhanced green fluorescent protein–tagged IRF8, generated small interfering RNA knockdowns of IRF8 expression in a mouse B cell lymphoma cell line, and examined the effects of a null mutation of IRF8 on B cells. Each approach identified activation-induced cytidine deaminase (AICDA) and BCL6 as targets of transcriptional activation. Chromatin immunoprecipitation studies demonstrated in vivo occupancy of 5′ sequences of both genes by IRF8 protein. These results suggest previously unappreciated roles for IRF8 in the transcriptional regulation of B cell GC reactions that include direct regulation of AICDA and BCL6.